Efficiency analysis of nano light emitting diodes - Witzigmann, Bernd (Proceedings - 2014 International Conference on Electromagnetics in Advanced Applications, ICEAA 2014, 2014)
Semiconductor light emitting diodes (LEDs) are light sources with the highest broadband electro-optical efficiency of any solid state device. They are an ideal choice for energy efficient lighting applications. In this paper, the light extraction efficiency of nano-LEDs is studied based on electromagnetic modeling. As main result, it is shown that the optical extraction efficiency analysis requires detailed knowledge of the electronic properties of the LED, such as internal quantum efficiency and local absorptivity. These properties are studied for a III-nitride based nanowire array LED.
CRIS-Team Scopus Importer:2021-06-11